The Сategory of Nationality of Literature as a Subject of Comprehension in the History of Russian Criticism of the 19th Century - Svyatoslavsky, Alexey V. (Dva veka russkoj klassiki, 2024)
The article examines the history of the formation of the concept of “nationality” as an aesthetic category in Russian criticism of the 19th century. The research attempts to identify certain constants in understanding nationality as an ethnic-social concept and aesthetic category in fiction and to trace its transformations in changing historical conditions concerning certain ideological discourses and cultural paradigms. The works of V. G. Belinsky, A. S. Khomyakov, N. A. Dobrolyubov, I. V. Kireevsky, N. A. Berdyaev, N. K. Mikhailovsky, the correspondence of P. A. Vyazemsky and articles by A. S. Pushkin demonstrates some examples of understanding nationality. Despite the variety of approaches to the interpretation of nationality in later times, the most adequate remains the thoughts contained in the works of Belinsky and the Slavophiles.